Holocene thermokarst and pingo development in the Kolyma Lowland (NE Siberia). (10th July 2018) - Wetterich, Sebastian; Schirrmeister, Lutz; Nazarova, Larisa; Palagushkina, Olga; Bobrov, Anatoly; Pogosyan, Lilit; Savelieva, Larisa; Syrykh, Liudmila; Matthes, Heidrun; Fritz, Michael; Günther, Frank; Opel, Thomas; et al.
Abstract: Ground ice and sedimentary records of a pingo exposure reveal insights into Holocene permafrost, landscape and climate dynamics. Early to mid‐Holocene thermokarst lake deposits contain rich floral and faunal paleoassemblages, which indicate lake shrinkage and decreasing summer temperatures (chironomid‐based T July ) from 10.5 to 3.5 cal kyr BP with the warmest period between 10.5 and 8 cal kyr BP. Talik refreezing and pingo growth started about 3.5 cal kyr BP after disappearance of the lake. The isotopic composition of the pingo ice (δ 18 O − 17.1 ± 0.6‰, δD −144.5 ± 3.4‰, slope 5.85, deuterium excess −7.7± 1.5‰) point to the initial stage of closed‐system freezing captured in the record. A differing isotopic composition within the massive ice body was found (δ 18 O − 21.3 ± 1.4‰, δD −165 ± 11.5‰, slope 8.13, deuterium excess 4.9± 3.2‰), probably related to the infill of dilation cracks by surface water with quasi‐meteoric signature. Currently inactive syngenetic ice wedges formed in the thermokarst basin after lake drainage. The pingo preserves traces of permafrost response to climate variations in terms of ground‐ice degradation (thermokarst) during the early and mid‐Holocene, and aggradation (wedge‐ice and pingo‐ice growth) during the late Holocene.